Engineering Technology of White Shrimp (Litopenaeus vannamei) Intensive System Culture with the Suplementation of Phytase Enzyme in the Diet - Diana Rachmawati; Istiyanto Samidjan (Fisheries and Marine Science Faculty - Jenderal Soedirman University)
This study aims to examine the effect of phytase enzyme in the diet on digestibility of growth of white shrimp (Litopenaeus vannamei) raised in intensive system culture. Research on the suplementation of phytase enzymes in L. vannamei diet is very important to hydrolyze phytic acid in vegetable ingredients as a source of diet protein so as to increase the efficiency of diet utilization to support growth of vaname shrimp. The shrimp used in the research had average weight of 1,19±0,06 g/shrimp. The diet contained 38% of protein and 3200 Kcal DE/kg with various doses of phytase enzyme suplementation, namely: A (0 U/kg diet), B (500 U/kg diet), C (1000 U/kg diet) and D (1500 U/kg diet). Observed parameters were digestibility of phosphore (ADCF), disgetibility of protein (ADCP), efficiency of diet utilitzation (EFU), protein efficiency ratio (PER), diet convesion ratio (FCR) relative growth rate (RGR), and survival rate (SR). The suplementation of phytase enzyme in the diet significantly influenced (P<0.01) on ADCF, ADCP, EFU, PER, FCR, RGR; however, it did not significantly influence on SR of white shrimp. The best treatment result was the suplementation of 1000 U/kg diet phytase enzyme (treatment C). The optimum dose of phytase enzyme in the diet was 867, 920, 923, 915, 1000 and 1000 U/kg of diet respectively for ADCF, ADCP, EFU, PER, FCR, RGR. Based on those result the suplementation of phytase enzyme can increase the growth of white shrimp.